Impact of preparing nursing students to deliver a parent-based sexual health intervention on attitudes and intentions for sexual health education and parent communication counseling: a mixed methods study - Deidra Carroll Coleman; Anitra Frederick; Stanley Cron; Christine Markham; Vincent Guilamo-Ramos; Diane Santa Maria (BMC, 2023)
Abstract Background Nurses are well positioned to promote sexual health but are not adequately prepared in their nursing programs to engage families on this topic and often lack the knowledge and confidence necessary to counsel families about sexual health communication. The purpose of this study was to determine how facilitating a parent-based sexual health intervention would impact nursing students' attitudes and intentions about sexual health education and parent communication counseling. Methods Using an embedded mixed-methods design, which integrated a quasi-experimental framework, we examined the impact of participation in a parent-based sexual health intervention among 126 baccalaureate nursing students enrolled in a community/public health nursing clinical course. Independent t-tests, chi-squared tests, and the Mann-Whitney U test were used to compare intervention and control groups at baseline. Multiple linear regression was used to compare the groups for pre-post changes. Qualitative content analysis was used to analyze exit interview transcripts. Results We found statistically significant differences in nursing students' confidence to teach sexual health (p = < 0.001), satisfaction with skills as a sexual health educator (p = < 0.001), beliefs about the efficacy of parent-adolescent communication for reducing negative sexual outcomes among adolescents (p = < 0.001), and intentions to counsel parents on sexual health (p = < 0.001), with greater improvements in the intervention group than in the control group. Furthermore, we found statistically significant differences in nursing students' intentions to counsel parents about the HPV vaccine (p = < 0.01) and to endorse the HPV vaccine (p = < 0.05), with greater improvements in the intervention group than in the control group. Across all survey categories, qualitative findings confirmed improvements seen on the pre-post survey. Conclusion Providing evidence-based adolescent sexual health training, including sexual health education content and discussion strategies, can prepare nursing students to strongly endorse sexual health communication and HPV vaccination uptake and to counsel parents on initiating and navigating these conversations with their youth. Our project exemplifies how a nursing program could organize an immersive experience, or elective within a specialty area, that aligns with the competency-based approach endorsed by the American Association of Colleges of Nursing. Trial registration This study was registered with ClinicalTrials.gov (NCT02600884) on 09/01/2015; the first participant was recruited on 09/29/2015.